Architecture and function analysis of integrated energy service stations considering cyber‐physical integration. Issue 4 (17th November 2021) - Liu, Haoyu; Wang, Qi; Tang, Yi
Abstract: With the continuing development of the energy internet (EI), the high complexity of multi‐energy coupling and the dramatic increase in cyber‐physical integration impose stricter requirements on the planning and construction of multi‐energy systems. The construction of a new energy hub through the intensive use of existing power substation resources is one of the feasible approaches for satisfying these requirements. Integrated energy service stations (IESSs), which comprise substations, multi‐energy conversion stations, data centres, communication base stations, and other functional units, constitute the emerging generation of energy and information control centres. IESSs are capable of all‐in‐one monitoring and energy optimization, and can effectively manage regional energy services involving various energy requirements. This study initially proposes two feasible schemes to realize IESSs: entity IESSs, which require replanning and construction, and virtual IESSs, which involve transformation through existing substation resources. Thereafter, based on the requirements of three types of users, that is high‐energy‐consumption users, highreliability users, and high‐comfort users, the necessity of IESSs in the construction of the EI is analysed in depth. Furthermore, the feasibility of constructing an IESS based on existing power grid resources and the direction for the future development are discussed.